2020
DOI: 10.1177/0018720820957466
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control When Using an Industrial Lower Limb Exoskeleton: Impact of Reaching for a Working Tool and External Perturbation

Abstract: Objective To investigate postural control related to a lower limb exoskeleton (Chairless Chair) when (a) reaching for a working tool, and (b) an external perturbation occurs. Background Lower limb exoskeletons aiming to reduce physical load associated with prolonged standing may impair workers’ postural control and increase the risk of falling. Method Forty-five males were reaching for an object (3-kg dumbbell) at the lateral end of their reaching area without the exoskeleton in upright standing (STAND) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Further hazards connected to the use of exoskeletons are ergonomic hazards. Operators wearing such devices often have limited mobility and are therefore unable to avoid the collision with falling objects [72,[74][75][76][77][78][79][80], or, contrastingly, they may perform improper movements or overexert themselves, thus provoking muscle damages, i.e., tears [72]. Moreover, the additional weight of the devices and their dimensions may lead to complications, i.e., damages caused by the difference in art-leg kinematic [72,74,81,82], musculoskeletal issues [72,[74][75][76][77]81,83], muscular fatigue [48][49][50]53,57,58], minor damages and pressure injuries [72,74,75,77,81], nerve compression [72,74], respiratory fatigue caused by a decreased chest excursion and by an increased chest pressure [72,74,81], discomfort [48][49][50]52,53,57], cardiovascular issues, wrong weight redistribution between different body parts…”
Section: Exoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Further hazards connected to the use of exoskeletons are ergonomic hazards. Operators wearing such devices often have limited mobility and are therefore unable to avoid the collision with falling objects [72,[74][75][76][77][78][79][80], or, contrastingly, they may perform improper movements or overexert themselves, thus provoking muscle damages, i.e., tears [72]. Moreover, the additional weight of the devices and their dimensions may lead to complications, i.e., damages caused by the difference in art-leg kinematic [72,74,81,82], musculoskeletal issues [72,[74][75][76][77]81,83], muscular fatigue [48][49][50]53,57,58], minor damages and pressure injuries [72,74,75,77,81], nerve compression [72,74], respiratory fatigue caused by a decreased chest excursion and by an increased chest pressure [72,74,81], discomfort [48][49][50]52,53,57], cardiovascular issues, wrong weight redistribution between different body parts…”
Section: Exoskeletonmentioning
confidence: 99%
“…Eye fatigue due to the different focal lengths [56,58] Possibility to instruct workers in real time Psychophysical overload due to work intensification [67] Despecialization of job duties Damages caused by the decreased competences [67] Inadequate employee training Damages caused by unexpected events [67] Possibility to capture images and record videos Fear of privacy violation [55,57] Difference between the virtual images and the real world Damages due to reduced movement coordination [57,58] Muscle fatigue [72,[74][75][76]78,[80][81][82] Damages connected to spine overload [72,79] Postural stress [72,77,79,82] Cardiovascular diseases [72,74,82] Damages caused by the difference in art-leg kinematic [72,74,81,82] Minor damages and pressure injuries [72,74,75,77,81] Nerve compression [72,74] Respiratory fatigue caused by a decreased chest excursion and by an increased chest pressure [72,74,81] Discomfort [72,[74]…”
Section: Significant Information Loadmentioning
confidence: 99%
“…For example, when using this type of EXO for chair-like support, lower limb muscle activity decreased 36% during a simulated bolting task at two heights (Kong et al, 2022), and the percentage of body weight supported by the feet decreased 64% and gastrocnemius muscle activity decreased 75% compared to standing during a simulated seated assembly task (Luger et al, 2019). Leg-support EXOs can also result in unintentional and undesirable outcomes related to balance or fall risk such as a greater susceptibility to losses of balance after external perturbations during simulated seated assembly work (Steinhilber et al, 2022), and a reduced "feeling of safety" while walking on a treadmill (Groos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many upper- and lower-limb wearable exoskeletons, which are mechanical structures worn on the body to enhance the power of the wearer, have been developed and studied to reduce exposure to prolonged stationary standing and sitting tasks [ 15 , 16 ]. Wearable exoskeletons are actively used in various fields, such as in military and industrial settings, as components of rehabilitation assistance, and on automobile assembly lines because the exoskeletons do not require separate spaces [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luger et al [ 25 ] and Steinhilber et al [ 16 ] investigated the effects of wearing the Chairless Chair passive lower-limb exoskeleton on muscle activity and perceived discomfort during screwing, cable-mounting, and clip-fitting tasks at varying working distances. The results showed that the activities of the ES (erector spinae) and GAS (gastrocnemius) muscles were significantly lower during high siting and low sitting EXO tasks, respectively, than during standing (without EXO).…”
Section: Introductionmentioning
confidence: 99%